EFFECT OF ORGANIZATIONAL CULTURE ON THE PERFORMANCE OF BENUE BREWERY MAKURDI BENUE STATE - Garba, Adamu (International Journal of Research -GRANTHAALAYAH, 2020)
This study examined the effect of organizational culture on performance of Benue Brewery in Makurdi. The population of this study is made up of 214 employees of Benue Brewery Limited Makurdi. Using the census approach, the population of 214 was adopted as the sample for the study. The data for the study was collected by the use of structured questionnaire while the hypotheses for the study were tested using regression analysis. The researcher found a positive effect of constructive organizational culture on profitability and market share. The result also shows a positive effect of passive organizational culture on both profitability and market share. Finally, the result also shows a positive effect of aggressive organizational culture on market share. The study concludes that the elements of organizational culture can affect the performance of an organization. It therefore recommended that management should promote constructive and passive organizational culture since these types of organizational culture have the highest influence on organizational performance.